2017
DOI: 10.18203/issn.2455-4510.intjresorthop20172872
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of functional outcome of anterior cruciate ligament reconstruction using quadruple hamstring graft

Abstract: <p class="abstract"><strong>Background:</strong> Anterior cruciate ligament reconstruction is the most commonly reconstructed ligaments of the knee. This study attempts to analyse the functional outcome of ACL reconstruction and the parameters utilized commonly to assess the outcomes<span lang="EN-IN">.</span></p><p class="abstract"><strong>Methods:</strong> This is an analysis of 25 patients who underwent ACL reconstruction, who were operated by a single s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
8
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 9 publications
4
8
1
Order By: Relevance
“…Unpaired t test was done, and this difference was not statistically significant (p=0.361). Similar improvement were found in a previous study by using Quadrupled semitendinosus graft that Lysholm scoring significantly improved from mean preoperative scoring 58.76±15.29 to a mean postoperative score of 91.16±3.87 (Chodavarapu et al, 2017). [13] Islam et al [7] (2017) found in their study by using Tripled semitendinosus tendon graft Lysholm knee score significantly improved from mean preoperative scoring 52.64±4.256 to a mean postoperative score of 92.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Unpaired t test was done, and this difference was not statistically significant (p=0.361). Similar improvement were found in a previous study by using Quadrupled semitendinosus graft that Lysholm scoring significantly improved from mean preoperative scoring 58.76±15.29 to a mean postoperative score of 91.16±3.87 (Chodavarapu et al, 2017). [13] Islam et al [7] (2017) found in their study by using Tripled semitendinosus tendon graft Lysholm knee score significantly improved from mean preoperative scoring 52.64±4.256 to a mean postoperative score of 92.…”
Section: Discussionsupporting
confidence: 89%
“…However, this association was not statistically significant (p=0.660). Chodavarapu et al (2017) observed anterior cruciate ligament reconstruction surgery with quadrupled hamstring grafts, [13] provides 72% excellent outcome to ACL injuries when the surgery is timed well, with sufficient graft thickness and good rehabilitation. Islam et al (2017) found in their study by using Tripled semitendinosus tendon graft, provides 86% Satisfactory (excellent and good) outcome.…”
Section: Discussionmentioning
confidence: 99%
“…This is similar to the study by Umar et al [7] who used BPB graft and reported mean preoperative Lysholm score of 58.19 ± 20.0 and 6 months postoperative score of 88.23 ± 12.17. Other studies whose researchers have found similar results include Bhati et al [15] and Chodavarapu et al [16] Our study utilized triple-weaved hamstring graft but Bhati and colleagues, and Chodavarapu et al used quadruple-weaved semitendinosus and gracilis grafts with similar outcomes [15,16] . Other studies have used horizontal hamstring grafts and some have compared it with patella tendon graft.…”
Section: Discussionsupporting
confidence: 58%
“…The grading system was obtained from the study of Misou et al [ 11 ] A Pakistani study found that more patients had excellent functional outcomes as calculated by the Lysholm knee scoring scale after ACL reconstruction [ 12 , 13 ]. In India, [ 14 ] a case series of 25 patients who underwent ACL reconstruction for a year and were operated on by a single surgeon found that the mean preoperative Lysholm score was 58.8 (fair 56%; bad 44%). This increased to 91.2 after surgery (excellent 72%; good 24%).…”
Section: Discussionmentioning
confidence: 99%
“…According to Chodavarapu and associates [ 14 ], the most common presurgical concern was instability. This supports the findings of Devgan and colleagues [ 15 ] who found that patients experienced persistent knee pain and instability before arthroscopic assisted ACL reconstruction.…”
Section: Discussionmentioning
confidence: 99%